Optimization of Ingredients upon Development of the Protective Polymeric Composite Coatings for the River and Sea Transport - Andriy Buketov; Serhii Yakushchenko; Abdellah Menou; Oleh Bezbakh; Roman Vrublevskyi; Yaroslava Kalba; Tetyana Cherniavska; Danylo Zhytnyk; Olha Danylyuk (Communications - Scientific letters of the University of Zilina, 2021)
It is proved that in order to increase the operational characteristics of parts of the river and sea transport, including their physical and mechanical properties, it is advisable to use the protective polymeric composite coatings. The effect of fillers on the flexural stresses of the developed epoxy composite was analyzed. The critical content of components was determined by the method of mathematical planning of the experiment: the synthesized powder mixture - 0.05 pts.wt., discrete fibers - 0.10 to 0.15 pts.wt. per 100 pts.wt. of epoxy oligomer ED-20. Introduction of such ingredients into the epoxy binder allows to increase the flexural stresses to σ f=77.4…78.6 MPa. The obtained results allow to create materials with improved values of physical and mechanical properties.